Книга путешествий - Битов Андрей Георгиевич (Библиотека "Дружбы народов", 1986)
Экземпляры: ф-13 (ретроконверсия) / Инвентарный номер: 17164 / Цена: 2.40 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 66 / ББК: 84(2Рос=Рус)6